(untitled) (Confluenţe Bibliologice, 2019)
The second part of the article dedicated to the great Russian composer N. A. Rimsky-Korsakov on his 175th birthday, deals with his brilliant masterpiece , The Legend of the Invisible City of Kitezh". This mysterious work related to church music culture (akathist, liturgy) has a deep philosophical and religious sense and is often compared to the musical innovations of Richard Wagner. The work describes the charming heroines of Rimsky-Korsakov’s work. The authors of the article, also, inform users about books and other famous works of composers that can be found in the Oﬃce of Musical Literature of SL USARB.